PENGARUH MOTIVASI TERHADAP KINERJA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA PT. NOK PRECISION COMPONENT BATAM - Ade Ade; Hazriyanto; Daris Purba (Journal of Innovation Research and Knowledge, 2026)
This study aims to examine and analyze the effect of motivation on employee performance with job satisfaction as a mediating variable in the production department of PT. Nok Precision Component Batam. This research uses a quantitative approach with a causal explanatory design. The research population was all production employees, totaling 150 people. The sampling was conducted using a simple random sampling technique with a sample size of 54 respondents. Primary data collection was carried out through the distribution of Likert-scale questionnaires (1-5). The collected data were analyzed using the Structural Equation Modeling - Partial Least Square (SEM-PLS) method through SmartPLS 3.0 software. The results of hypothesis testing prove that: (1) Motivation has a positive and significant effect on job satisfaction; (2) Motivation has no significant direct effect on employee performance; (3) Job satisfaction has a positive and significant effect on employee performance; and (4) Job satisfaction fully mediates the effect of motivation on employee performance. These findings conclude that providing motivation from the company does not automatically improve technical performance on the production floor if the motivation fails to create a sense of satisfaction within the employees first.